The identification and analysis of the factors affecting energy consumer behaviour - Trzęsiok, Joanna; Słupik, Sylwia (Identyfikacja i analiza czynników wpływających na zachowanie konsumentów energii, 2019)
The article aims to identify energy consumer behaviour, particularly in the area of energy saving. Trends in contemporary consumption, including energy consumption, reveal that an increasing number of consumers make purchase decisions in a conscious and rational manner. This is caused by the globalization and integration of markets, evolving lifestyles and social trends. Modern energy consumers are also concerned with their footprint on the natural environment. Using data, gathered in the survey, the authors conducted principal component analysis, selecting 12 new variables that represent the basic types of energy consumer behaviour focused around rational and sustainable energy consumption. The study also examined the factors that significantly influenced consumer attitudes and behaviour. The results showed that generally energy saving actions were not related to the income factor. Education, employment status and age also had a very limited influence on energy consumer attitudes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 113-126
Keywords: energy consumption; energy consumer behaviour; principal component analysis; konsumpcja energii; zachowanie konsumentów energii; analiza głównych składowych; PCA